Analisis Isi Kualitatif Grup Facebook “Info Cepat Ngawi Peduli”, sebagai Sumber Media Informasi Masyarakat Kabupaten Ngawi - David Prasetya (IKIP Budi Utomo Malang, 2020)
The development of technology in the media field is increasing diversly. Facebook is one of the media that can share information. Info Cepat Ngawi Peduli is a group formed on the basis of the wishes of the people of Ngawi Regency for problems or social events that occur in Ngawi Regency. This type of qualitative research by collecting data using observation and documentation, documenting content in groups and then analyzed. The results of the study showed that information commonly shared by group users was Social Information, Criminal Information, Traffic Information and Entertainment. In meeting the information needs of the Info Cepat Ngawi Peduli group, it becomes a source of information exchange, while the information needs of the Info Cepat Ngawi Peduli group are cognitive, affective, personal integration, social integration and imaginary needs. It is expected that in this study, group administrators and group moderators will filter to prevent violations that have become the rules of the group, knowing content or submissions that are the most discussed, criminal information and traffic information.